Civil Passions : Moral Sentiment and Democratic Deliberation - Krause, Sharon R. (Book collections on Project MUSE., 2008)
In this book Sharon Krause argues that moral and political deliberation must incorporate passions, even as she insists on the value of impartiality. Her work provides a systematic account of how passions can generate an impartial standpoint that yields binding and compelling conclusions in politics.